2018
DOI: 10.1002/jbm.a.36537
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring degradation rates of silk fibroin scaffolds for tissue engineering

Abstract: In tissue regenerative medicine, developing tunable degradation rate of biomaterials for predictive functional outcomes remains critical. The implanted scaffolds should degrade gradually along with the tissue regeneration, and the optimal degradation rate of scaffold depends on the tissue type to be regenerated. Herein, the tunable degradation rates of silk fibroin (SF) scaffolds were fabricated through controlling dissolution, hydrolyzing conditions, and freeze-drying. The pore size, water adsorption capacity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 44 publications
(45 reference statements)
1
55
0
Order By: Relevance
“…[10] [11] Currently, control of degradation rate over time is crucial for scaffolds used in tissue-engineering applications and is a key factor influencing the structure and properties of the scaffold. [12] [13] [14] Elastin-like recombinamers (ELRs) are considered to be advanced biomaterials since they are multifunctional materials that can be tailored to exhibit a wide range of properties as well as functionalities such as cell adhesion, cell signaling, elasticity and biodegradability. [15] [16] [17] Moreover, they can be genetically engineered to exhibit complex biological functionalities as well as stimuli-responsiveness and, more specifically, they can change their physicochemical properties as a result of a change in a given stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…[10] [11] Currently, control of degradation rate over time is crucial for scaffolds used in tissue-engineering applications and is a key factor influencing the structure and properties of the scaffold. [12] [13] [14] Elastin-like recombinamers (ELRs) are considered to be advanced biomaterials since they are multifunctional materials that can be tailored to exhibit a wide range of properties as well as functionalities such as cell adhesion, cell signaling, elasticity and biodegradability. [15] [16] [17] Moreover, they can be genetically engineered to exhibit complex biological functionalities as well as stimuli-responsiveness and, more specifically, they can change their physicochemical properties as a result of a change in a given stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…[ 26 ] Further, the biodegradation rates of silk films can be further tuned if needed depending on the desired tissue engineering application. [ 13b,27 ] To characterize the silk rolls, we also studied the biomechanics of the rolls (Figure S11, Supporting Information). The compressive modulus was 5.86 ± 0.36 MPa for SRs and 4.65 ± 1.63 MPa for pSRs, respectively, considerably higher than that for the hydrogel systems.…”
Section: Resultsmentioning
confidence: 99%
“…[ 11 ] However, for these materials, it was still challenging to adjust the biomechanics and biocompatibility. Silk protein has been widely used in tissue engineering and regeneration [ 12 ] due to its biocompatibility, controllable biodegradability, [ 13 ] tunable biomechanical properties, [ 14 ] and low inflammatory effects. [ 15 ] Recently, spider silk and chitosan were coupled together to enable a self‐folding tube, which showed potential as nerve guidance conduits, allowing the adherence and differentiation of neuronal cells inside the tubes, and the growth of neurites.…”
Section: Introductionmentioning
confidence: 99%
“…Silk fibroin is a widely known natural biomaterial acquired from B. mori cocoons and contains alanine, glycine and serine [42,43]. Previous reports have shown that silk fibroin has excellent biocompatibility, strong mechanical properties and low degradation rate [50][51][52]. BM-MSCs produced new ECM on patterned silk fibroin surfaces [53].…”
Section: Discussionmentioning
confidence: 99%